New records of riverweeds (Podostemaceae) from the tropical Andes (Ecuador and Colombia): getting our feet wet to bypass collection bias in Neotropical rivers - Bedoya, Ana M.; Pérez, Álvaro J. (Phytotaxa, 2023)
Two species of Podostemaceae, with few previous georeferenced records West of the Andes in northern South America, are reported across the Andes in the region. Our records document a wider range of the Podostemaceae in the tropical Andes and result from recent floristic explorations in Andean rivers in Ecuador and Colombia. These new records are of use for future research in the group, as well as for conservation projects in rivers. We call for international collaborative projects supporting local collectors and institutions in Latin America to bolster research in the under-collected river plants and assess their distribution. We extend the invitation to local scientists to get their feet wet and collect plants in river-rapids and waterfalls.